Board characteristics and non-financial information disclosures under Directive 2014/95/EU: Evidence from Portugal (International Journal of Business Innovation, 2023)
This study analyses the effect of the Board of Directors’ characteristics on the disclosure of non-financial information by Portuguese listed companies, in the context of the Directive 2014/95/EU. To this end, a non-financial information disclosure index was built, based on the Directive disclosure requirements and a set of items defined in the GRI standards. The results obtained show that the diversity of nationalities in the Board has a positive effect on the non-financial information disclosed regarding all topics provided for in the Directive, except for information on the business model. The academic background of the Board, i.e., the presence of members with master’s or doctoral degrees has a positive effect on the disclosure of information on social matters. Board size, Board independence, CEO duality, Board gender diversity and Board activity do not appear to influence non-financial information disclosures. The findings support the need to consider less studied Board characteristics, as the diversity of nationalities and academic background, as dimensions of corporate governance that influence the quality of non-financial reporting.
Keywords: non-financial reporting; corporate governance; sustainability; board diversity